Application of the Teaching at The Right Level (TARL) Learning Method in the Physical Education Curriculum at SMK Negeri 8 Semarang - Prayogo, Wahyu Kridho; Herlambang, Tubagus (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. The independent curriculum is a program designed to facilitate the restoration of learning. This study aims to explore the implementation of the Independent Curriculum alongside the TaRL Approach within the PJOK learning process at SMK Negeri 8 Semarang in 2024. Materials and Methods. The research approach employed is descriptive qualitative. This study involved four subjects and sample informants: the vice principal for curriculum, facilities and infrastructure, PJOK teachers, and students from SMK Negeri 8 Semarang. The techniques for data collection involved observation, interviews, and documentation. Results. The results of this study include profile data, as well as the vision and mission of SMK Negeri 8 Semarang. Additionally, it encompasses information on school identity, facilities, and infrastructure. Notably, SMK Negeri 8 Semarang has been implementing the Merdeka Curriculum since the 2022/2023 academic year. Conclusion. The implementation of the independent curriculum at SMK Negeri 8 Semarang has been executed effectively, despite encountering various obstacles and challenges along the way. Improvements should focus on enhancing facilities and infrastructure, along with providing guidance to students who may lack motivation in their learning efforts. This is a more concise recommendation paragraph. It is advisable to conduct additional studies to assess the long-term effects of TaRL, to compare it with alternative approaches, and to investigate its influence on students' motivation and social skills. Furthermore, exploring the adaptation of TaRL to various subjects, enhancing parental involvement, creating learning modules, and conducting case studies in different schools are also crucial areas for investigation.